SAT0498 Importance of Anti- Cyclic Citrullinated Peptide as A Marker Differentiating Hepatitis C Related Arthropathy from Rheumatoid Arthritis. (15th July 2016) - Abdel Noor, R.A.; Gabr, M.; Alnaggar, M.; Enaba, M.; Hammad, S.
Abstract : Background: Hepatitis C arthropathy is one of the most important extra-hepatic manifestations of HCV. Its clinical presentation is rheumatoid like in about 30% of the cases and the differentiation between both is very important and difficult at the same time as the treatment is completely different. Anti-cyclic citrullinated peptide (Anti- CCP) antibodies can be used as serological markers in differentiation between them but many studies have variable and non-conclusive results concerning its importance. Objectives: The aim of this study is to determine whether anti- CCP antibody is helpful alone in discriminating patients with HCV-associated arthropathy from patients with rheumatoid arthritis. Methods: In this cross sectional comparative study we included 70 subjects, from Tanta University Hospital, Egypt and divided them into four groups: 30 Rheumatoid arthritis patients not infected with HCV, 15 HCV patients with typical polyarthritis like RA without erosions or rheumatoid nodules, 15 HCV patients without arthropathy and 10 Normal subjects as a control group. We measured the level of Anti-CCP and RF in all groups. Results: By the end of the study we found that anti-CCP was positive in 83.3% of RA group, 66.7% of HCV with arthropathy group, 40% of HCV without arthropathy group and in 30% of normal control group and there was a significant difference between RA group and HCV without arthropathy and control group, but there was no significant difference between RA and HCV arthropathy However during the comparison between the four groups as regard the degree of positivity of anti-CCP level there was a big difference in the degree of positivity in RA group and HCV arthropathy where 19 (63.3%) were strong positive in RA groups while only (20%)were strong positive in HCV related arthropathy. Conclusions: Anti CCP can be a used as an early step in differentiating RA from HCV related arthropathy. If its level is strong positive this can highly suggest early rheumatoid arthritis but if the level is moderately positive or weak positive or even negative it is not enough alone as a marker differentiating RA from HCV related arthropathy. References: Michele Bombardieri, Cristiano Alessandri, Giancarlo Labbadia ea. Role of anti-cyclic citrullinated peptide antibodies in discriminating patients with rheumatoid arthritis from patients with chronic hepatitis C infection-associated polyarticular involvement. Arthritis Res Ther 2004;6(2):R137–41. E Or, A C, Ayten Y, N Gr-P, Hulagu S. The positivity of rheumatoid factor and anti-cyclic citrullinated peptide antibody in nonarthritic patients with chronic hepatitis c infection. Rheumatol International 2010;30(4):485–8. M.Elnadry, Abdel-Rashed M, M.A.Abdel-Monem, S.El-Eter, Fathy W. Anti-Cyclic Citrullinated Peptide Frequency in Egyptian Patients with Chronic Hepatitis C Virus Infection with and without Articular Manifestation Journal of American Science 2013;9(11). Disclosure of Interest: None declared